Enhancing savonius rotor model with additional grooves on hydrokinetic turbine performance - Sampelawang, Petrus; Salam, Nasaruddin; Sule, Luther; Tarakka, Rustan (Eastern-European Journal of Enterprise Technologies, 2024)
Hydrokinetic turbines use different rotors for technological and economic reasons. Even though it performs poorly, vertical-axis hydrokinetic turbines use the Savonius rotor. The object of research is a Savonius rotor model with additional grooves. The study addresses the need to improve the efficiency and overall performance of Savonius rotor models in hydrokinetic turbines, which are widely used for harnessing energy from flowing water currents. The problem involves understanding how different groove configurations affect the aerodynamic behavior and energy extraction efficiency of the Savonius rotor in hydrokinetic turbine applications. The test results revealed that incorporating grooves led to notable improvements in efficiency (ɳ) and coefficient of drag (CD). Grooved blades exhibited a maximum efficiency of 30.97 % and a maximum drag coefficient of 2.71. Notably, blades with a groove width of 12.5 mm emerged as the optimal model, demonstrating an efficiency peak of 35.66 % and a drag coefficient 3.08. This indicates a substantial increase in efficiency by 4.69 % and a corresponding rise in the drag coefficient by 0.37 for grooved blades. The grooves on grooved blades increase friction, improving performance. Grooved rotor blades improve turbine performance significantly. Savonius rotor models in hydrokinetic turbines extract more energy by optimizing groove width and arrangement to maximize drag coefficient and efficiency. This research affects hydrokinetic turbine design and optimization for renewable energy generation. Engineers and designers can improve the performance and efficiency of the Savonius rotor model in hydrokinetic turbine applications by applying this study’s findings